As leis fundamentais do Maranhão: densidade jurídica e valor constituinte. A contribuição da França Equinocial ao constitucionalismo americano - Santana, José Cláudio Pavão (2008)
The present work deals with the formation of the constitutionalism in the American continent. It argues the daily payconstitutionalism and the nature of the Basic Laws of the Maranhão as contribution to the constitutionalism